No effects of carbohydrate ingestion on muscle metabolism or performance during short-duration high-intensity intermittent exercise - Vigh-Larsen, J. F.; Kruse, D. Z.; Moseholt, M. B.; Hansen, L. G. B.; Christensen, A.-L. L.; Bæk, A.; Andersen, O. E.; Mohr, M.; Overgaard, K. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Carbohydrates are critical for high-intensity exercise performance. However, the effects of carbohydrate supplementation on muscle metabolism and performance during short-duration high-intensity intermittent exercise remain inadequately explored. Our aim was to address this aspect in a randomized, counterbalanced, double-blinded crossover design. Eleven moderately-to-well-trained males performed high-intensity intermittent cycling receiving carbohydrate (CHO, ~55 g/h) or placebo (PLA) fluid supplementation. Three exercise periods (EX1-EX3) were completed comprising 10 × 45 s at ~105% Wmax interspersed with 135 s rest between bouts and ~20 min between periods. Repeated sprint ability (5 × 6 s sprints with 24 s recovery) was assessed at baseline and after each period. Thigh muscle biopsies were obtained at baseline and before and after EX3 to determine whole-muscle and fiber-type-specific glycogen depletion. No differences were found in muscle glycogen degradation at the whole-muscle (p = 0.683) or fiber-type-specific level (p = 0.763-0.854) with similar post-exercise whole-muscle glycogen concentrations (146 ± 20 and 122 ± 15 mmol·kg-1 dw in CHO and PLA, respectively). Repeated sprint ability declined by ~9% after EX3 with no between-condition differences (p = 0.971) and no overall differences in ratings of perceived exertion (p = 0.550). This was despite distinctions in blood glucose concentrations throughout exercise, reaching post-exercise levels of 5.3 ± 0.2 and 4.1 ± 0.2 mmol·L-1 (p < 0.001) in CHO and PLA, respectively, accompanied by fivefold higher plasma insulin levels in CHO (p < 0.001). In conclusion, we observed no effects of carbohydrate ingestion on net muscle glycogen breakdown or sprint performance during short-duration high-intensity intermittent exercise despite elevated blood glucose and insulin levels. These results therefore question the efficacy of carbohydrate supplementation strategies in high-intensity intermittent sports.